Biomonitoring of heavy metals using intertidal mollusks in East Johor coastal waters - Rahman, Md. Mokhlesur; Fuad, Miskon; Yunus, Kamaruzzaman (2014)
Interspecies, inter-tissue and interspatial dissimilarities of trace metals in particular body parts of Saccostrea cucullata, Thais clavigera and Nerita chameleon from the east coast Johor of Peninsular Malaysia were investigated. Bivalve mollusc S. cucullata evidenced to be a worthy bioindicator for Zn and Cu while the two gastropod molluscs, T. clavigera for Cd and Se, and N. chameleon for Pb, Mn, Fe and Sr. The prominent concentration of metals originate in T. clavigera may be the outcome of biomagnification transfer from the S. cucullata on which they feed while for N. chameleon, it might be resulting from their herbivorous feeding behavior on algae on rocks which they graze. The metal accumulation patterns indicate consistent enrichment of essential metals in soft tissue. Values of operculum to tissue ratio and shell to tissue higher than unity in T. clavigera indicate that operculum had higher affinities for Pb, Mn and Se while shell had higher affinities for Fe, Co and Sr. In N. chameleon, values of OTR and STR higher than unity displayed that operculum and shell had similar higher affinities for Cd, Fe, Co and Sr. Significant interspatial variations (p<0.05 and p<0.01) in trace metals were noted. Sites with relatively high concentrations of the contaminant metals Hg, Cu, Pb and Zn are linked to their close proximity to industrial activities and municipal spots. The pollutant levels witnessed on the particular sites are still inferior to certain highly polluted sites globally. Assessment of metal concentration with maximum permissible limits of toxic metals in food shown the values were well within safety levels, except for Cu and Zn in S. cucullata.